2008
DOI: 10.1186/1471-2164-9-607
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptional profiling reveals Streptococcus agalactiae genes controlled by the MtaR transcription factor

Abstract: Background: Streptococcus agalactiae (group B Streptococcus; GBS) is a significant bacterial pathogen of neonates and an emerging pathogen of adults. Though transcriptional regulators are abundantly encoded on the GBS genome, their role in GBS pathogenesis is poorly understood. The mtaR gene encodes a putative LysR-type transcriptional regulator that is critical for the full virulence of GBS. Previous studies have shown that an mtaR -mutant transports methionine at reduced rates and grows poorly in normal huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 41 publications
(64 reference statements)
1
33
2
Order By: Relevance
“…CpsY shares homology (83% identity) with a LysR family transcriptional regulator of S. mutans (MetR), as well as to proteins in S. iniae (CpsY) and S. agalactiae (MtaR) that regulate methionine transport (25), amino acid metabolism (26), and resistance to neutrophilmediated killing and survival in vivo (27)(28)(29). This led us to hypothesize that CpsY functions as a transcriptional regulator of GAS metabolism required for survival in human host blood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CpsY shares homology (83% identity) with a LysR family transcriptional regulator of S. mutans (MetR), as well as to proteins in S. iniae (CpsY) and S. agalactiae (MtaR) that regulate methionine transport (25), amino acid metabolism (26), and resistance to neutrophilmediated killing and survival in vivo (27)(28)(29). This led us to hypothesize that CpsY functions as a transcriptional regulator of GAS metabolism required for survival in human host blood.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis confirmed that CpsY activity is associated with low-level repression of mntE and Spy0500, as well as induction of emm1 and mur1.2. Further examination of the Spy0500 sequence found 79% identity to the N-acetylmuramoyl-L-alanine amidase encoded by the murA gene characterized as regulated by CpsY in S. iniae (29) and MtaR in S. agalactiae (26). Thus, it appears that the sequence annotated in the MGAS5005 genome as murA (M5005_Spy0548) does not correspond to the homolog of the CpsY-regulated murA characterized in other streptococci.…”
Section: Spy0500])mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, CmbR (FhuR) and MetR were shown to control sulfur amino acid metabolism genes in L. lactis and methionine genes in S. mutans and Streptococcus agalactiae, respectively (12,19,(56)(57)(58). A phylogenic analysis of these proteins and their homologues from 14 Streptococcus genomes, presented in Fig.…”
Section: Identification Of Two Ltrrs Involved In Sulfur Amino Acid Sumentioning
confidence: 99%
“…Rather, CpsY was renamed MtaR in S. agalactiae (48) and MetR in Streptococcus mutans (50) because of its influence on methionine biosynthesis and uptake. However, the regulatory function of MtaR in S. agalactiae appears to extend beyond methionine metabolism (6).…”
mentioning
confidence: 99%